Khái niệm về hành vi tìm kiếm thông tin của sinh viên - Bùi, Hà Phương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The paper presents an overview of theoretical studies on information-seeking behavior of undergraduate students. It also analyzes the importance of understanding the concept of information-seeking behavior for academic libraries and each student. This overview is the basis for carrying out practical studies on the information-seeking behavior of undergraduate students in learning, research, and entertainment activities.